Antibiotics during Intrauterine Balloon Tamponade Is Associated with a Reduction in Endometritis - Wong, Melissa S.; Dellapiana, Gabriela; Greene, Naomi; Gregory, Kimberly D. (American Journal of Perinatology, 2019)
Objective To evaluate whether prophylactic antibiotics at the time of placement of an intrauterine balloon tamponade (IBT) is associated with a reduction in postpartum endometritis.Study Design Retrospective cohort study of patients who received an IBT from January 1, 2012, to December 12, 2016. Patients were included if the IBT remained in place at least 2 hours and excluded if chorioamnionitis was present. Patients who received prophylactic antibiotics at the time of IBT placement were compared with those who did not.Results A total of 149 subjects received an IBT; 36 were excluded due to early removal or chorioamnionitis. Of the remaining, 59 received prophylactic antibiotics and 54 did not. Baseline characteristics were similar between the groups except mode of delivery. The majority (65%) of those who did not receive prophylactic antibiotics had a cesarean delivery (p = 0.03). The overall incidence of endometritis was 15%. The incidence of endometritis was greater among those patients who did not receive prophylactic antibiotics compared with those who did (5 vs. 26%; p < 0.002; odds ratio [OR]: 6.53; 95% confidence interval [CI]: 1.76–24.25). This association remained after adjustment for mode of delivery and receiving group B Streptococcus antibiotics prior to delivery (adjusted OR: 5.9; 95% CI: 1.58–22.35).Conclusion Prophylactic antibiotics were associated with a reduction in postpartum endometritis among patients receiving an IBT.
Keywords: intrauterine; tamponade; Bakri; postpartum hemorrhage; endometritis; antibiotics